PERAN GURU DALAM MENGEMBANGKAN KARAKTER DISIPLIN MELALUI SEKOLAH RAMAH ANAK SISWA KELAS IV DI SDN BAHAGIA 05 - Risma Yanti; Suharjuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims (1) to describe the role of teachers in developing students' disciplined character through the Child-Friendly School approach in class IV of SDN Bahagia 05, Bekasi Regency. (2) To describe the obstacles faced by teachers in developing disciplined character through Child-Friendly School at SDN Bahagia 05, Bekasi Regency. This study uses a qualitative descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The methods used in data analysis are data collection, data reduction, and drawing conclusions. The conclusion of this study is that there are four roles of teachers in developing disciplined attitudes through Child-Friendly School at SDN Bahagia 04 referring to the Teachers and Lecturers Law, namely: teachers as educators, teachers as trainers, teachers as discipline developers, and teachers as mentors. There are three factors that hinder teachers in developing disciplined character through Child-Friendly School at SDN Bahagia, namely: limited number of teachers, negative influence of peer relationships, and family factors.